PELAYANAN PUBLIK DI KECAMATAN UJUNG BATU KABUPATEN ROKAN HULU TAHUN 2013 (STUDI REKOMENDASI IZIN MENDIRIKAN BANGUNAN) - Putra, Julfan Dwi; ", Muchid (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2014)
The recommendation of building permit from sub-district head is requirement of the building permit in Rokan Hulu Regency. Building permit commendation of the sub-district at the Ujung Batu sub-district Office had the authority of Ujung Batu sub-district. Therefore Ujung Batu subdistrict government should provide a good service to the public in the making of building permits recommendations.This research is a descriptive study using a qualitative approach as a tool of analysis. This research was conducted in Ujung Batu sub-district, Rokan Hulu. This research was using interviews with key informants as information objects that aim to achieve the goal in order to get information in this research. Data used of this research is primary data and secondary data obtained through observation and interviews with key informants in this research.Service Implementation of the building permit recommendation from government officials to the citizens service users is still not good. It fairness is based on the clarity and certainty of that the service is still lacking, it is not efficient in service, is not evenly distributed in the service, and still less of an employee disciplinary for the service of building permit recommendations that resulted is not timely in service. As for some of the factors that influence the implementation process of building permit service recommendations in District Ujung Batu, namely : a) There is still a lack of support facilities to the community service activities. Equipment also needs to be adapted to the development of existing technology to facilitate and speed up the service process. b) There is still a lack of personnel service clerk technical control of the main task, so that sometimes the service becomes less effective. c) There are still of officials who are still not disciplined.Keywords: Public Service, Subdistrict, Building Permit Recommendation